Pengaruh Motivasi Kerja dan Penilaian Kinerja terhadap Kepuasan Kerja Karyawan pada PT Pos Indonesia (Persero) Malang - Reni Sancoko; Armanu Thoyib (Jurnal Ilmiah Mahasiswa FEB, 2012)
The research was conducted in PT Pos Indonesia (Persero) Malang. Currently Human Resources is not only seen as complementary in the network chain to the achievement of corporate goals alone, HR also needs to be empowered to be able to be a resource of qualified and trained to achieve the expected performance of the Company. The study design used is explanatory research, and use this type of quantitative research using multiple regression statistical tools and validity test. The results showed that work motivation (X1), performance appraisals (X2), simultaneously or jointly significant effect on the variable Job satisfaction (Y) employees of PT Pos Indonesia (Persero) Malang. This means that PT Pos Indonesia (Persero) Malang has been implemented with good work motivation and performance appraisal so that the level of job satisfaction is high. Partially motivation and performance appraisal positive and significant effect on job satisfaction of employees of PT Pos Indonesia (Persero) Malang.   Keyword : Employee Satisfaction, Work Motivation, Performance Appraisal